Dietary Patterns and Whole Plant Foods in Aging and Disease - Dreher, Mark L. (Nutrition and Health, 2018)
This text provides a comprehensive review of the latest research on the effects of dietary patterns and whole plant foods on general health, aging, and cardiometabolic disease risk from major prospective cohort studies and randomized controlled trials (RCTs) and their meta-analyses. The book extensively assesses the effects of lifestyle, dietary patterns, and specific whole plant foods on the quality of aging; the impact of fiber-rich foods on colonic microbiotia and weight regulation, the effects of which influence the quality of aging; the effects of fiber-rich diets on the aging gastrointestinal tract; and the role of dietary patterns and specific whole plant foods on coronary heart disease, hypertension, chronic kidney disease, stroke and type 2 diabetes. Figures are extensively used to highlight findings and tables summarizing food composition dietary patterns and whole plant foods. Tables summarizing meta-analyses and representative cohort studies and RCTs provide state-of-the-art coverage of the important effect of dietary patterns and whole plant foods on aging and cardiometabolic diseases. Dietary Patterns and Whole Plant Foods in Aging and Disease will serve as a very useful, state -of -the-art resource for dietitians, physicians, nurses, food industry scientists, researchers, naturopathic doctors, educators and their students interested in the role of dietary patterns and specific whole plant foods on aging and disease.